2023
DOI: 10.3390/life13040965
|View full text |Cite
|
Sign up to set email alerts
|

The Replicative DnaE Polymerase of Bacillus subtilis Recruits the Glycolytic Pyruvate Kinase (PykA) When Bound to Primed DNA Templates

Abstract: The glycolytic enzyme PykA has been reported to drive the metabolic control of replication through a mechanism involving PykA moonlighting functions on the essential DnaE polymerase, the DnaC helicase and regulatory determinants of PykA catalytic activity in Bacillus subtilis. The mutants of this control suffer from critical replication and cell cycle defects, showing that the metabolic control of replication plays important functions in the overall rate of replication. Using biochemical approaches, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Another way is via a central carbon metabolism that, in E. coli , can: (1) promote DnaA to its active DnaA-ATP form and its binding to oriC by cAMP (a regulator of this part of metabolism) [ 49 ]; (2) suppress the defects of the dnaA46 mutant by changes in pyruvate and acetate metabolism [ 50 ]; (3) inhibit DnaA conversion to DnaA-ATP and its binding to oriC (via acetylation of DnaA, with acetyl-CoA and acetyl-phosphate as donors) (for references see [ 51 ]). Evidence for the involvement of the central carbon metabolism in DNA replication in Bacillus subtilis includes: (1) subunits of pyruvate dehydrogenase (PdhC) and related enzymes bind the origin of replication region, DnaC and DnaG inhibit the initiation of replication; (2) mutations in the genes of central carbon metabolism suppress initiation and elongation defects in dnaC , dnaG , and dnaE mutants; (3) mutations in gapA (which encodes glyceraldehyde 3-phosphate dehydrogenase) perturb the metabolic control of replication; (4) pyruvate kinase (PykA) can both inhibit initiation and stimulate elongation via proposed interactions with DnaC, DnaG, and DnaE as modulated, perhaps, by phosphorylation [ 51 , 52 ].…”
Section: Does the Initiation Hyperstructure Contain Glycolytic Enzymes?mentioning
confidence: 99%
“…Another way is via a central carbon metabolism that, in E. coli , can: (1) promote DnaA to its active DnaA-ATP form and its binding to oriC by cAMP (a regulator of this part of metabolism) [ 49 ]; (2) suppress the defects of the dnaA46 mutant by changes in pyruvate and acetate metabolism [ 50 ]; (3) inhibit DnaA conversion to DnaA-ATP and its binding to oriC (via acetylation of DnaA, with acetyl-CoA and acetyl-phosphate as donors) (for references see [ 51 ]). Evidence for the involvement of the central carbon metabolism in DNA replication in Bacillus subtilis includes: (1) subunits of pyruvate dehydrogenase (PdhC) and related enzymes bind the origin of replication region, DnaC and DnaG inhibit the initiation of replication; (2) mutations in the genes of central carbon metabolism suppress initiation and elongation defects in dnaC , dnaG , and dnaE mutants; (3) mutations in gapA (which encodes glyceraldehyde 3-phosphate dehydrogenase) perturb the metabolic control of replication; (4) pyruvate kinase (PykA) can both inhibit initiation and stimulate elongation via proposed interactions with DnaC, DnaG, and DnaE as modulated, perhaps, by phosphorylation [ 51 , 52 ].…”
Section: Does the Initiation Hyperstructure Contain Glycolytic Enzymes?mentioning
confidence: 99%
“…The PEPut domain of PykA is not required for royalsocietypublishing.org/journal/rsob Open Biol. 13: 230220 the catalytic activity of the enzyme [67,107]. However, it interacts with CAT via a hydrogen bond between E208 (CAT) and L536 (PEPut), as shown in a structural study of the highly homologous (72.5% identity) Geobacillus stearothermophilus PykA [108].…”
Section: Pyka Allosteric Regulationmentioning
confidence: 99%
“…when the CAT-PEPut interaction is impeded) (figure 4, right panel). In addition to these distinct effects of PykA conformers on initiation, it was shown that (i) PykA physically interacts with the polymerase DnaE via its CAT domain when the replication enzyme is bound to primed DNA [67], (ii) PEPut modulates the strength of this interaction and its effect on the DnaE polymerase activity [66,67], and (iii) DnaE is early recruited at replication origins during initiation [61]. We thus suggest from these data that However, while the T-state conformer dramatically increases DnaE activity and causes early initiation, the R-state conformer allows a proper polymerase activity and initiation timing.…”
Section: Pyka-driven Mcrmentioning
confidence: 99%
See 2 more Smart Citations